2023
DOI: 10.1186/s12014-023-09395-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum IgG glycosylation patterns in rheumatoid arthritis

Abstract: Background RA is a common chronic and systemic autoimmune disease, and the diagnosis is based significantly on autoantibody detection. This study aims to investigate the glycosylation profile of serum IgG in RA patients using high-throughput lectin microarray technology. Method Lectin microarray containing 56 lectins was applied to detect and analyze the expression profile of serum IgG glycosylation in 214 RA patients, 150 disease controls (DC), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…They identified significantly decreased galactosylation in RA patients by evaluating the primary sequences of approximately 1400 oligosaccharides from 46 IgG samples. With the rapid development of novel characterization techniques in glycomics in the past decade, the reduction in IgG galactosylation levels in RA has been verified in dozens of studies, making it the first wellestablished glycan feature of RA [145,146]. In addition to reduced IgG galactosylation, other glycomic alterations, including decreased sialylation and increased fucosylation, were also observed in RA patients, as reviewed by Flevaris and Kontoravdi [100].…”
Section: N-glycan Biomarkers In Autoimmune Diseasesmentioning
confidence: 97%
“…They identified significantly decreased galactosylation in RA patients by evaluating the primary sequences of approximately 1400 oligosaccharides from 46 IgG samples. With the rapid development of novel characterization techniques in glycomics in the past decade, the reduction in IgG galactosylation levels in RA has been verified in dozens of studies, making it the first wellestablished glycan feature of RA [145,146]. In addition to reduced IgG galactosylation, other glycomic alterations, including decreased sialylation and increased fucosylation, were also observed in RA patients, as reviewed by Flevaris and Kontoravdi [100].…”
Section: N-glycan Biomarkers In Autoimmune Diseasesmentioning
confidence: 97%
“…The altered glycosylation of IgG was strongly connected with pathogenesis and changes in the course of the disease [110]. It is of particular importance since it is widely known that altered sialylation in RA contributes to the regulation of arthritogenicity [111]. Lundström et al have suggested that changes in the glycome of serum can be considered potential indicators of MTX clinical response prediction [112].…”
Section: Molecular and Cellular Consequences Of Sialome Targetingmentioning
confidence: 99%
“…Glycosylation occurring at the antibody Fc region has the potential to modify its binding affinity to innate immune receptors, thereby initiating signaling cascades that give rise to various antibody-dependent responses, such as inflammation, antibody-dependent cellular cytotoxicity, and antibody-dependent cellular phagocytosis ( 3 ). Given the critical biological functions associated with these responses, extensive studies have explored the association between Ig glycosylation and various diseases ( 4 , 5 , 6 , 7 ). Consequently, the development of sensitive and specific analytical methods for studying Ig glycopeptides has tremendous potential to uncover their biomedical impacts.…”
mentioning
confidence: 99%